2003
DOI: 10.1111/j.1365-2362.2003.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide screen in obese pedigrees with type 2 diabetes mellitus from a defined Dutch population

Abstract: A genome scan was performed in obese type 2 diabetes mellitus pedigrees to identify susceptibility loci involved in obesity-driven type 2 diabetes mellitus. We studied the 20% most obese diabetes pedigrees from a confined Dutch population from around the town of Breda. Previously we, and others, have already shown that a susceptibility locus influencing obesity in diabetes may reside on chromosome 18p11. We now report evidence to also suggest linkage for type 2 diabetes in these obese pedigrees on chromosome r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…25 It has been also reported that the region on the short arm of chromosome 11 (11p15) shows suggestive evidence for linkage to obese type 2 diabetes, which also harbors the SUR1 gene. 26,27 On the other hand, it is noteworthy that human adipocytes express SUR1 that regulates intracellular Ca +2 and, consequently, exerts coordinate control over lipogenesis and lipolysis, suggesting a potential role for the human adipocyte SUR1 in modulating energy storage and thereby potentially contributing to obesity. 28 In our study, the patients with SNP in the SUR1 gene (AGG→AGA; Arg1273Arg) had significantly higher triglyceride levels than the patients without SNP, support the hypothesis that SUR1 has a potential role in mediating lipogenesis and lipolysis in the adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…25 It has been also reported that the region on the short arm of chromosome 11 (11p15) shows suggestive evidence for linkage to obese type 2 diabetes, which also harbors the SUR1 gene. 26,27 On the other hand, it is noteworthy that human adipocytes express SUR1 that regulates intracellular Ca +2 and, consequently, exerts coordinate control over lipogenesis and lipolysis, suggesting a potential role for the human adipocyte SUR1 in modulating energy storage and thereby potentially contributing to obesity. 28 In our study, the patients with SNP in the SUR1 gene (AGG→AGA; Arg1273Arg) had significantly higher triglyceride levels than the patients without SNP, support the hypothesis that SUR1 has a potential role in mediating lipogenesis and lipolysis in the adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The CDK4 gene lies in a chromosomal region of interest for cancer predisposition [ 4 ] and for obesity-associated T2D genes [ 5 ]. It is known to be involved in cell cycle regulation, and represents a strong candidate gene for tumor and/or cancer genetic predisposition [ 6 - 8 ]. Although the effect size of any potential gene risk variant in any tumor/cancer is not predictable until is tested, we can deduct from the present study that the CDK4 IVS4-nt40 AA genotype does not independently and significantly contribute as a major significant risk variant to tumors/cancer in our Italian dataset.…”
Section: Discussionmentioning
confidence: 99%
“…CDK4 has mitogenic [ 2 ] through phosphorylation of target proteins [ 4 ]. The chromosome 12q12-q14 region has been shown by a genome scan to be in linkage to bladder cancer [ 5 ], as well as to obesity-associated type 2 diabetes genes [ 6 ]. Previous studies have reported differential CDK4 expression in tumors such as gliosarcoma, mantle cell lymphoma and squamous cell carcinoma [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…CDK4 null mice have decreased body weight and develop T2D due to inability of beta cells to proliferate (Rane et al, 1999). Furthermore, CDK4 lies on chromosome 12q.14, the locus in linkage to obesity‐associated T2D genes (van Tilburg et al, 2003). Of note, we have previously shown that CDK4 IVS4‐nt40AA genotype plays a role in obesity‐associated tumor/cancer risk predisposition (Meenakshisundaram and Gragnoli, 2009).…”
mentioning
confidence: 99%